2006
DOI: 10.2175/106143006x119521
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Human Health Risk Assessment

Abstract: INTRODUCTIONThis literature review of the risk assessment process addresses both ecological and human receptors. The review covers the risk assessment literature including methodology, analysis, interpretation, uncertainty, and regulatory guidance.Companion reviews in this volume that address the effect of pollutants and their fate and transport processes in the aquatic environment overlap the discipline of risk assessment and, therefore, the reader is urged to review these sections as they will not be covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Periphytic diatoms comprise a large number of species with various ecological preferences. Because of their position in the food webs and their short life cycle, their quick responses to environmental changes, and their easy sampling (allowing for standardization for temporal and spatial comparisons), periphytic diatoms have widely been accepted as a robust indicator to evaluate environmental stress and anthropogenic effects in ecological investigations and monitoring researches (Lange-Bertalot, 1979;Steinberg and Schiefele, 1988;Van Dam et al, 1994;Andren, 1999;Duong et al, 2007;Morin et al, 2010;Biksey et al, 2011;Grinham et al, 2011;Mearns et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Periphytic diatoms comprise a large number of species with various ecological preferences. Because of their position in the food webs and their short life cycle, their quick responses to environmental changes, and their easy sampling (allowing for standardization for temporal and spatial comparisons), periphytic diatoms have widely been accepted as a robust indicator to evaluate environmental stress and anthropogenic effects in ecological investigations and monitoring researches (Lange-Bertalot, 1979;Steinberg and Schiefele, 1988;Van Dam et al, 1994;Andren, 1999;Duong et al, 2007;Morin et al, 2010;Biksey et al, 2011;Grinham et al, 2011;Mearns et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Its introduction to water by natural processes and human activities is of potential concern. Contamination of ground and surface water by As from soil and aquifers poses a significant threat to human health (Förstner and Wittmann, 1981;Biksey et al, 2011). Therefore, it is important to fully understand the fate and transport characteristics of As in sediment or aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…Ciliated protozoa are an important contributor to the microplankton communities in functioning of the microbial food web by mediating the flux of elements and energy from bacteria or microalgae to higher trophic levels Xu et al, 2011aXu et al, , 2011b. With short generation times and delicate external pellicles, rapid responses to environmental stress, anthropogenic impact greater than many other eukaryotic organisms, and high tolerance to extreme biotopes, protozoa have been widely used to evaluate water quality in many aquatic ecosystems (Biksey et al, 2011;Jiang et al, 2007;Mearns et al, 2011;Xu et al, 2002;. Many previous investigations have shown that ciliated protozoa may be used as robust indicators for environmental bioassessment, in particular, monitoring water quality in marine ecosystems Tan et al, 2010;Xu et al, 2002;.…”
Section: Introductionmentioning
confidence: 99%